(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article is devoted to the problem of psychological and pedagogical accompaniment of socialization of younger schoolchildren in educational institutions. The main components of school socialization of children are considered. The importance of adequate socialization of elementary school students in the formation of a situation of success in education and upbringing is determined. The level of manifestation of school anxiety by younger schoolchildren is studied. The conclusion is made on the need to combine the efforts of the family and the school in solving the problems of socialization of younger schoolchildren.